Eco-abuse of rights five years later (Nueva Epoca, 2020)
This article addresses the problem of putting into practice by the courts the figure of abuse of rights in relation to «rights of collective incidence» (art. 14 in fine, Civil and Commercial Code). The analysis of the jurisprudence shows that the employment has not yet been consolidated into a true judicial doctrine, but the construction process has already begun and for its continuity a better understanding of the role —within the framework of the CCC design lines Project— is required, to improve the understanding of the profile of the figure, which includes four key points: the genealogy of the norm, its differentiation with the case of conflicts between individual and collective rights,the guidelines for its operation and the judicial claims to which it may give rise.
Keywords: abuse of rights; collective rights; Civil and Commercial Code